(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Serological status of thyroid hormones is important among chronic kidney disease patients. Objective: The purpose of the present study was to see the status of thyroid hormones among chronic kidney disease patients. Methodology: This cross-sectional study was done From January 2013 to December 2013 in the Department of Nephrology, Dhaka Medical College Hospital. A total of 50 diagnosed cases of adult male with different stages of CKD (CKD stage 3, 4, 5 and 5D) patients along with age-matched 51 healthy individuals were included. Serum Thyroid hormone T3 done by [1251] RIA kit, T4 done by T4 [1251] RIA kit, TSH level done by Turbo TSH [1251] IRMA kit. Result: A total number of 101 patients were recruited for this study of which 51 cases were in the group A and the rest of the 50 cases were in the group B. The mean serum T3 level was found 1.85±0.7 nmoL/L in group A and 2.79±0.55 nmoL/L in group B (p<0.05) which indicated that low serum T3 level was significantly associated with CKD. The mean serum T4 level was found 104.65±34.9 nmol/L in group A and 138.8±31.5 nmol/L in group B (p<0.05). Serum TSH level of the study patients showed that the mean serum TSH level was found 4.23±4.6 mIU/L in group A and 2.06±2.5mIU/L in group B (p<0.05). Conclusion: In conclusion the mean with SD of serum level of T3, T4 and TSH were significantly associated with chronic kidney disease. Journal of National Institute of Neurosciences Bangladesh, July 2022;8(2):147-151